Confinement and type of penning affects the interval to estrus and synchrony of estrus in gilts after altrenogest - Davis, Duane L.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We compared the effects of outside vs inside and individual vs group penning on the interval to estrus after synchronization of estrus with altrenogest. Altrenogest (15 mg/day) was fed for 14 days and penning treatments were initiated after the last altrenogest treatment. All groups were exposed to a boar (2 hr/day) for 3 days, beginning the day after last altrenogest, and then twice daily estrous detection was initiated. Outside penning shortened the interval to estrus after altrenogest. Synchrony of estrus was not affected by treatment but there was a tendency for gilts penned outside to exhibit estrus more synchronously.
Keywords: Swine; Confinement; Penning; Altrenogest